"PONTA PORÃ - POLCA, CHURRASCO E CHIMARRÃO": A REPRESENTAÇÃO DA FRONTEIRA NA OBRA DE ELPÍDIO REIS - CAVICHIOLI, Natalia Aparecida Dante; FREIRE, Zelia Ramona Nolasco dos Santos (ANAIS DO ENIC, 2017)
-